Hubungan Pengetahuan Produk Minuman Kopi Terhadap Keputusan Pemilihan Minuman Di Coffee Shop “404 Eatery And Coffee” - Jessica Rizky Darda; Mariani; Ridawati (Jurnal Sains Boga, 2019)
Nowadays drinking coffee in a coffee shop become a trend and a lifestyle in Indonesia. At the first coffee shop is one kind of a food and beverages industries that only focus for served only coffee. But, as long as food and beverages industries getting bigger, coffee shops did some innovation to their menus. They are not only serving coffee, coffee shops has another option for non coffee people. The innovation has bring the new problem for consumer and it is called as a purchase decision. The purchase decision has some factors that maybe can impact to itself, one of them is product knowledge. This research is about to find the correlation between product knowledge and purchase decision in coffee shop “404 eatery and coffee”. This research used explanatory survey methods and used questionnaire as an instrument. The instrument separated into two questionnaire, the first questionnaire is about product knowledge which has fouth indicator :product attributes, the functional benefits, the pshycologic benefits, and points of product. For the second questionnaire it has fifth indicator : introduction of needs, information searching, alternative evaluates, buying decision and post buying decision. The result of this research showed that x variable (product knowledge) has a significant correlation to y variable (purchase decision) with the positively and significantly of regression result (0,98) Keywords: Product knowledge, purchase decision, coffee shop, coffee